YouTube Kids: English Vocabulary Learning Media for Early Childhood - Hidayah, Siti Nur; Astuti, Wili (Universitas Muhammadiyah Surakarta, 2025)
This study aims to determine the use of YouTube Kids in English vocabulary learning for early childhood, specifically group B children at Bakti Sawahan Islamic Kindergarten. The method used in this study was qualitative with a descriptive approach. The subjects in this study were children in group B at Bakti Sawahan Islamic Kindergarten. Data were collected through observation, interviews with teachers, and documentation of learning activities. After the data is collected there are several stages in analyzing data. The first stage is data reduction, which is the process of sorting, selecting, and simplifying data so that the data collected is the data needed and relevant for use in research. After that, data presentation (Display Data) is carried out, where the filtered information is then compiled and described in a descriptive form so that it can be read and understood easily. The final stage in this process is verification, where researchers review all the analyzed data to ensure its accuracy, then summarize the important findings that constitute the final results of the research.The results showed that using YouTube Kids as a learning medium can improve children's English vocabulary mastery. Educational videos with engaging visuals and clear pronunciation help children more easily understand and remember new vocabulary. Furthermore, children also demonstrated enthusiasm and active participation during the learning process. The conclusion of this study is that YouTube Kids is an effective and engaging medium for English vocabulary learning for early childhood, particularly in creating a fun and interactive learning environment.